The Realization Of Interpersonal Meanings Of Conversation Texts In Developing English Competencies And Interlanguage For Grade X - Khalim, Abdul; Warsono, Warsono (Universitas Negeri Semarang, 2017)
This research examined Interpersonal Meaning in conversation texts in grade x English textbooks â€œDeveloping English Competencies and Interlanguage. This study was a qualitative research employing a descriptive comparative method. The data were taken from the printed versions of an electronic English textbooks â€œDeveloping English Competenciesâ€ by Ahmda Dody et al 2008 and â€œInterlanguageâ€ by Joko Priyono et al 2008. Four conversation texts of each English textbook were selected from the whole texts that have the same topics based on the basic competence of the school based curiculum. Thus, the total data were eight conversation texts. This research resulted several findings. The first finding is the realization and similarities and differences of interpersonal meaning in both texts consisting status, affect and contact and the appraisal system consisting affect, judgment and appreciatiation. There were similarities between conversation texts of two English textbooks. The similarities were found between texts A1 and B1, A2 and B2 and A3 and B3 their status was equal and their social distance was frequent contact and high affective involvement. Second, the differeences were found between A4 and B4. From the appraisal system of attitude (affect, judgment and appreciation), texts from textbook A and those from textbook B showed good attitudes, which can be proof by the fact that the conversation texts in both conversation textbooks mostly use positive clauses more than negative one in realizing the interpersonal meaning (tenor).